Hazards and opportunities - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Hazards and opportunities - farming livelihoods in dryland Africa: lessons from Zimbabwe compiled by Ian Scoones et al available from CTA